Plankton Community in Ogan River, Kertapati District, Palembang, South Sumatra - Marson Marson; Elva Dwi Harmilia (Universitas Muhammadiyah Palembang, 2021)
Research on Plankton Community in The Waters of Ogan River Kertapati District, Palembang, South Sumatra Province, has been conducted from March to April 2018. This study aimed to identify the plankton community, i.e., abundance, diversity index, dominance index, similarity index between stations, and describe pollution level conditions based on saprobic coefficient. Sampling in this study using purposive random sampling method at five observation stations with three sampling locations, respectively. The physical and chemical parameters of the waters include temperature, brightness, current speed, pH, Dissolved Oxygen (DO), nitrates, and phosphates. The composition of plankton consists of 47 Genera derived from 8 Classes, with a total abundance value in March ranging from 13-27 ind./L, and the total value of abundance in April 2018 has a range of values of 12-21 ind./L. Plankton diversity index values in about 1.87-2.98 indicate the stability of the moderate biota community. Based on the index of plankton dominance with a range of 0.05-0.21, no species dominate other species or D = 0(<0.5). In contrast, the index of plankton similarity between stations shows the communities between stations are relatively different (<50%). The water quality of the Ogan River based on saprobic coefficients is light to very light.